All About Medical Journals and Articles - Shankar, C Vidya (Journal of Nepal Paediatric Society, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–>DOI = 10.3126/jnps.v28i1.1405 J. Nepal Paediatr. Soc. Vol.28(1) p.30-31